An optimized purple corn cob extract as an ingredient for the development of maize-based extrudates with novel characteristics - Rolandelli, Guido; Favre, Leonardo Cristian; Aguirre-Calvo, Tatiana Rocío; Farroni, Abel Eduardo; Buera, María del Pilar; Dos Santos Ferreira, Cristina (Elsevier, 2023)
Purple corn cobs (PCC) are normally discarded although containing valuable components of potential application in the development of foods and ingredients. Optimum extraction conditions for PCC bioactive compounds were defined considering maximum antioxidant activity (AA), anthocyanins concentration (TAC), and total phenolic content (TPC). The optimized PCC extract (Opt-PCC) was added to a maize-based extruded formulation, and the obtained products were compared with a control sample without extract regarding their color, TPC, AA, physical properties, water adsorption isotherms, thermal transitions, and microstructure. Besides significantly modifying the color of extrudates, the addition of Opt-PCC increased their physical stability since higher glass transition temperatures were obtained when compared to the control at similar water contents. Differences in water sorption behavior could be attributed to the hygroscopicity of the compounds present in the extract. The incorporation of Opt-PCC increased TPC and AA of the extrudates by 14 and 4 times, respectively. The results confirmed a significant increase in the functional properties and physical stability of the extrudates with the addition of Opt-PCC, encouraging its use as a natural ingredient in the development of novel foods with improved characteristics.